Empowering Elderly Through Productive Elderly Exercise Program and Creative Industry Training Based Oon Local Wisdom in Kenagarian Sariak, Sungai Pua District, Agam Regency - Nelson, Sonya; Muchlis, Arif Fadli; Sari, Dessi Novita (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2024)
The area targeted by PKM is Nagari Sariak, Sungai Pua District, Agam Regency, which has a fairly large elderly population. As for the partner's problems: (1) The activities at the elderly posyandu are classified as monotonous so there is a lack of interest in participants coming, the posyandu activities are only reflected in the process of checking the health of the elderly, for example in weighing, checking blood pressure, sometimes also checking cholesterol and uric acid. There is still a lack of activities aimed at improving physical fitness and exercise for the elderly, which until now is rarely done. This is also due to the lack of competent infrastructure to provide counseling and training in order to create a physically and spiritually healthy society. Activities at Posyandu are less varied and there is no special emphasis for elderly participants in carrying out exercise. Therefore, it is necessary to provide counseling and training about physical fitness, especially exercise for the elderly. The target to be achieved is an understanding of 1) sports, especially exercise for the elderly, as well as the proper and correct implementation of exercise for the elderly. Meanwhile, the second problem (2), concerns employment, especially for the elderly without potential, most of whom are elderly who are no longer working even though they still want to work. Some elderly people are still less productive, which has the consequence of reduced income which can lead to elderly poverty. activities through Training of Trainers (TOT) by providing material through lectures, then continued with direct practice. The results achieved are an increase in the level of health, physical fitness and increased knowledge and skills of elderly people in the field of crafts